2012
DOI: 10.1002/hep.25891
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic activation of glypican-3 by c-Myc in human hepatocellular carcinoma

Abstract: Glypican-3 (GPC3) is a heparan sulfate proteoglycan that has an important role in cell growth and differentiation, and its function in tumorigenesis is tissue-dependent. In hepatocellular carcinoma (HCC), the overexpression of GPC3 has been demonstrated to be a reliable diagnostic indicator. However, the mechanisms that regulate the expression and function of GPC3 remain unclear. The oncoprotein c-Myc is a transcription factor that plays a significant role in more than 50% of human tumors. We report here that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 31 publications
4
51
2
Order By: Relevance
“…C-myc is also considered to be oncogene and frequently overexpressed in HCC [39][40][41]. Our present results revealed that Ang II enhanced C-myc immunofluorescent expression in HCC cell lines and the expression was predominantly cell nucleus.…”
Section: Discussionsupporting
confidence: 61%
“…C-myc is also considered to be oncogene and frequently overexpressed in HCC [39][40][41]. Our present results revealed that Ang II enhanced C-myc immunofluorescent expression in HCC cell lines and the expression was predominantly cell nucleus.…”
Section: Discussionsupporting
confidence: 61%
“…Work from our laboratory has also shown that, in addition to being a marker of HCC, GPC3 stimulates the growth of this malignancy by promoting canonical Wnt signaling (Capurro et al, 2005). This finding has been confirmed by others (Li et al, 2012). Studies of GPC3-null mice have also demonstrated that GPC3 regulates Wnt signaling in normal embryonic tissues (Song et al, 2005).…”
Section: Introductionsupporting
confidence: 68%
“…There is increasing evidence indicating that the structural requirements for GPC3 activity are cell type-specific, and its core protein is processed by a furin-like convertase. GPC-3 is expressed like a carcinoembryonic antigen, it stains dark brown deep within HCC tissues, and it is found in the cytoplasm and cell membrane (30). Immunohistochemistry has revealed oncofetal GPC- cells of distinct tumors (2).…”
Section: Gpc-3 In Relation To Disease Stage and Prognosismentioning
confidence: 99%